1997
DOI: 10.1111/j.1469-7793.1997.355bn.x
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Interactions of Cd2+ and a Carboxylate Blocker with the Rat ClC‐1 Chloride Channel and Its R304E Mutant in the Sf‐9 Insect Cell Line

Abstract: 1. Gating of the skeletal muscle chloride channel (ClC-1) is sensitive to extracellular pH. In this study, whole-cell recording of currents from wild-type (WT) ClC-1 and a mutant, R304E, expressed in the Sf-9 insect cell line was used to investigate further the nature of the pHsensitive residues. 2. Extracellular Cd¥ produced a concentration-dependent block of WT ClC-1 with an IC50 of 1·0 ± 0·1 mÒ and a Hill coefficient of 2·0 ± 0·3. This block was sensitive to external pH, reducing at low pH, with an apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
6
33
2
Order By: Relevance
“…First, these findings validate adequate space clamp uniformity even in naive fibers because ClC-1 channel gating was unaffected by loss of a significant fraction of cell capacitance originating from the T-tubule compartment. Second, previous studies demonstrated that ClC-1 gating is strongly influenced by chloride concentration (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001), pH (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001;Bennetts et al, 2007), nitric oxide (Lin et al, 2008), and with some controversy, the binding of adenosine derivatives (Bennetts et al, 2005Tseng et al, 2007;Zhang et al, 2008;Zifarelli and Pusch, 2008). Although we did not directly test if these factors modulate native ClC-1 channel activity in FDB fibers, our findings suggest that detubulation by formamide addition and withdrawal does not markedly perturb basal modulatory influences of these factors on ClC-1 gating.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…First, these findings validate adequate space clamp uniformity even in naive fibers because ClC-1 channel gating was unaffected by loss of a significant fraction of cell capacitance originating from the T-tubule compartment. Second, previous studies demonstrated that ClC-1 gating is strongly influenced by chloride concentration (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001), pH (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001;Bennetts et al, 2007), nitric oxide (Lin et al, 2008), and with some controversy, the binding of adenosine derivatives (Bennetts et al, 2005Tseng et al, 2007;Zhang et al, 2008;Zifarelli and Pusch, 2008). Although we did not directly test if these factors modulate native ClC-1 channel activity in FDB fibers, our findings suggest that detubulation by formamide addition and withdrawal does not markedly perturb basal modulatory influences of these factors on ClC-1 gating.…”
Section: Discussioncontrasting
confidence: 57%
“…(Fukuda and Kawa, 1977) at a concentration (250 µM) that had no effect on ClC-1 currents (Rychkov et al, 1997;unpublished data).…”
Section: Macroscopic Recordings Of Clc-1 Currentsmentioning
confidence: 99%
“…Studies on the pH dependence of ClC-1 current block by Cd 2ϩ , another group IIb cation with behavior similar to that of Zn 2ϩ , yielded a pK a value of 6.8, i.e. nearly identical to ours (23). The authors of that study suggested that histidine residues might be involved.…”
Section: Discussionmentioning
confidence: 60%
“…the R304E mutant (17). When we tested our present mutants, Cd 2ϩ was as effective on ⌬D13 as on the WT channel (IC 50 ϭ 1.1 Ϯ 0.1 mM (n ϭ 3) for ⌬D13 and 1.0 Ϯ 0.1 mM (n ϭ 3) for WT), whereas fs895X required higher concentrations of Cd 2ϩ to achieve the same level of block (IC 50 ϭ 2.7 Ϯ 0.2 mM, (n ϭ 5).…”
Section: Resultsmentioning
confidence: 99%
“…Data were collected, filtered at 3 kHz, and analyzed on an IBM-compatible PC using pCLAMP v6.0 software (Axon Instruments). Parameters such as time constants, apparent open probability, and IC 50 were determined as described previously (16,17). …”
mentioning
confidence: 99%